CCVP CIPT quick reference sheets - Wallace, Kevin, 1965- (Cisco Press, 2006)
CCVP CIPT Quick Reference Sheets (Digital Short Cut) Kevin Wallace, CCIE No. 7945 ISBN: 1-58705-321-7 As a final preparation tool providing a review of CIPT exam topics, the CCVP CIPT Quick Reference Sheets complement official Cisco curriculum, other books, or other exam preparatory material. This digital Short Cut provides readers with detailed, graphical-based information, highlighting the key topics on the latest CIPT exam in a quick-review format. These fact-filled Quick Reference Sheets allow certification candidates to get all-important information at a glance, helping them to focus their study on areas of weakness and to enhance memory retention of important concepts. The CCVP certification recognizes a candidate's ability to create an IP telephony solution that is transparent, scalable, and manageable. Earning a CCVP certification validates a robust set of skills in implementing, operating, configuring, and troubleshooting a converged IP network. The certification content focuses on Cisco Systems Unified CallManager, quality of service (QoS), gateways, gatekeepers, IP phones, voice applications, and utilities on Cisco routers and Cisco Catalyst switches. The Cisco IP Telephony (CIPT) exam tests the candidate's knowledge of voice-over-IP (VoIP) and public switched telephone network (PSTN) components and technologies and the candidate's ability to describe, install, configure, and support Cisco CallManager version 4.1 in a Cisco network, including such features as security and video. This Short Cut is derived from the print publication, Cisco IP Telephony Flash Cards and Exam Practice Pack, ISBN: 1-58720-128-3. Table of Contents: The Cisco CallManager IP Telephony Components Dial Plans IP Telephony Options IP Telephony Applications Administrative Utilities Cisco CallManager 4.x Enhancements.